Analysis of Ornamental Fish Marketing before and during the covid-19 pandemic in Balang Baru Village, Makassar City - Andi Ummung; Muhammad Adam Asgar; Andi Nur Apung Massiseng; Roswiyanti Roswiyanti (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Ornamental fish is one of the largest foreign exchange earners that have a strategic role in the Indonesian economy. During the COVID-19 pandemic, almost all economic sectors experienced a decline, including the marine and fisheries sectors. This study aims to examine how the impact of the COVID-19 pandemic on the marketing of ornamental fish in Balang Baru Village. The results showed that sales of ornamental fish before the pandemic were sold on a large scale with relatively uniform sizes and prices, while during the pandemic, sales were mostly done on a small scale or per head with prices that varied depending on size and color